Room Temperature Stable PspA-Based Nanovaccine Induces Protective Immunity - Wagner-Muñiz, Danielle A.; Haughney, Shannon L.; Kelly, Sean M.; Wannemuehler, Michael J.; Narasimhan, Balaji (Frontiers in Immunology, 2018)
Streptococcus pneumoniae is a major causative agent of pneumonia, a debilitating disease particularly in young and elderly populations, and is the leading worldwide cause of death in children under the age of five. While there are existing vaccines against S. pneumoniae, none are protective across all serotypes. Pneumococcal surface protein A (PspA), a key virulence factor of S. pneumoniae, is an antigen that may be incorporated into future vaccines to address the immunological challenges presented by the diversity of capsular antigens. PspA has been shown to be immunogenic and capable of initiating a humoral immune response that is reactive across approximately 94% of pneumococcal strains. Biodegradable polyanhydrides have been studied as a nanoparticle-based vaccine (i.e., nanovaccine) platform to stabilize labile proteins, to provide adjuvanticity, and enhance patient compliance by providing protective immunity in a single dose. In this study, we designed a room temperature stable PspA-based polyanhydride nanovaccine that eliminated the need for a free protein component (i.e., 100% encapsulated within the nanoparticles). Mice were immunized once with the lead nanovaccine and upon challenge, presented significantly higher survival rates than animals immunized with soluble protein alone, even with a 25-fold reduction in protein dose. This lead nanovaccine formulation performed similarly to protein adjuvanted with Alum, however, with much less tissue reactogenicity at the site of immunization. By eliminating the free PspA from the nanovaccine formulation, the lead nanovaccine was efficacious after being stored dry for 60 days at room temperature, breaking the need for maintaining the cold chain. Altogether, this study demonstrated that a single dose PspA-based nanovaccine against S. pneumoniae induced protective immunity and provided thermal stability when stored at room temperature for at least 60 days.